2010
DOI: 10.1002/em.20552
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mitochondria for cancer therapy

Abstract: Several recent insights into the roles of mitochondria in cancer have renewed efforts to develop nongenotoxic therapies targeting mitochondrial proteins and functions. Mitochondria are central hubs for intrinsic apoptotic pathways that are activated by cellular stress and injury, and as a consequence, cancers often have defects in these pathways. Bcl-2, the first identified regulator of apoptotic cell deaths, was discovered as an oncogene in human cancers. BCL-2 inhibits mitochondrial pathways of apoptosis thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 145 publications
2
58
0
Order By: Relevance
“…Mitochondria have been considered as anticancer drug targets and have a key function in the regulation of apoptosis. 25) Our results indicated that cladribine caused G 2 /M arrest in MCF-7 cells and that the combination of cladribine and gefitinib or dasatinib led to an accumulation of cells in the G 2 /M phases at the expense of the G 1 phase. Dasatinib induced G 1 arrest in MCF-7 cells.…”
Section: Discussionsupporting
confidence: 49%
“…Mitochondria have been considered as anticancer drug targets and have a key function in the regulation of apoptosis. 25) Our results indicated that cladribine caused G 2 /M arrest in MCF-7 cells and that the combination of cladribine and gefitinib or dasatinib led to an accumulation of cells in the G 2 /M phases at the expense of the G 1 phase. Dasatinib induced G 1 arrest in MCF-7 cells.…”
Section: Discussionsupporting
confidence: 49%
“…Bcl-2 is a major anti-apoptotic protein which protects cells from a wide variety of apoptotic stimuli (26). By contrast, Bax is a Bcl-2-like protein that binds to and antagonizes the protective effect of Bcl-2, rendering cells more sensitive to apoptosis (27). In the present study, we found that only the level of Bax in H28 cells was significantly elevated by BBI treatment.…”
Section: Discussionsupporting
confidence: 41%
“…Bcl-2 inhibits the mitochondrial pathways of apoptosis through local effects at the mitochondrial and endoplasmic reticulum membranes (32). Furthermore, Bcl-2 was reported to be overexpressed in most breast cancer cells (33,34).…”
Section: Discussionmentioning
confidence: 99%